PENGHAMBATAN QUORUM SENSING SEBAGAI ALTERNATIF TERAPI PENYAKIT INFEKSI YANG DISEBABKAN OLEH BAKTERI - Shofyatul Yumna Triana; Farida Juliantina Rachmawati (Universitas Islam Indonesia, 2005)
ABSTRACTThe latest discoveries in the field of microbiology have proved that bacteria communicate eachother. The process of cell to cell communication is called quorum sensing. Quorum sensing wasfirst discovered in two luminous bacteria called Vibrio harveyi and Vibrio fischeri. These bacteriaemit light in response to increase in cell population density. Density-dependent light production isaccomplished trough the release and detection of hormone-like molecules called autoinducers thataccumulate in the environment as the bacterial density increases. Quorum sensing is believed toregulate competence in development, sporulation, virulence factor induction, sporulation andnutrient flux along with other events in pathogenic bacterial infections. Recently, many scientisthave been doing research in the field of quorum sensing. If the signaling systems among thebacteria were able to be blocked, the dangerous effects from bacteria then possibly be prevented.In other word, if the quorum sensing mechanism were stopped, the disease can be prevented oreven cured instead of antibiotics use.Keyword : bacterial infection – quorum sensing - inhibiton